Trabecular bone anisotropy imaging with a compact laser-undulator synchrotron x-ray source. Issue 1 (December 2017) - Jud, Christoph; Braig, Eva; Dierolf, Martin; Eggl, Elena; Günther, Benedikt; Achterhold, Klaus; Gleich, Bernhard; Rummeny, Ernst; Noël, Peter; Pfeiffer, Franz; Muenzel, Daniela
Abstract Conventional x-ray radiography is a well-established standard in diagnostic imaging of human bones. It reveals typical bony anatomy with a strong surrounding cortical bone and trabecular structure of the inner part. However, due to limited spatial resolution, x-ray radiography cannot provide information on the microstructure of the trabecular bone. Thus, microfractures without dislocation are often missed in initial radiographs, resulting in a lack or delay of adequate therapy. Here we show that x-ray vector radiography (XVR) can overcome this limitation and allows for a deeper insight into the microstructure with a radiation exposure comparable to standard radiography. XVR senses x-ray ultrasmall-angle scattering in addition to the attenuation contrast and thereby reveals the mean scattering strength, its degree of anisotropy and the orientation of scattering structures. Corresponding to the structural characteristics of bones, there is a homogenous mean scattering signal of the trabecular bone but the degree of anisotropy is strongly affected by variations in the trabecular structure providing more detailed information on the bone microstructure. The measurements were performed at the Munich Compact Light Source, a novel type of x-ray source based on inverse Compton scattering. This laboratory-sized source produces highly brilliant quasi-monochromatic x-rays with a tunable energy.